2011
DOI: 10.1080/19942060.2011.11015350
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of a Compressor Cascade at Highly Negative Incidence

Abstract: ABSTRACT:The performance prediction of axial flow compressors and turbines still relies on the stationary testing of blade cascades. Most of the blade testing studies are done for operating conditions close to the design point or in off-design areas not too far from it. However, blade-and consequently engine-performance remain unexplored at relatively far off-design conditions, such as windmilling or sub-idle. Such regimes are dominated by blade operation under extremely low mass flows and rotational speeds th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The variables of i eq and δ eq herein can be gained by a typical correlation methodology developed by Lieblein [7] for conventional blades, which has been extensively employed by Banjac et al [9], McGlumphy [18], and Zachos et al [19]. The method can be expressed implicitly by Equations (10) and 11:…”
Section: Equivalent Values Of Incidence and Deviation Anglesmentioning
confidence: 99%
See 1 more Smart Citation
“…The variables of i eq and δ eq herein can be gained by a typical correlation methodology developed by Lieblein [7] for conventional blades, which has been extensively employed by Banjac et al [9], McGlumphy [18], and Zachos et al [19]. The method can be expressed implicitly by Equations (10) and 11:…”
Section: Equivalent Values Of Incidence and Deviation Anglesmentioning
confidence: 99%
“…Therefore, it is necessary to correct the correlations with off-reference conditions so as to apply the model under practical compressor circumstances. Based on the basic correlations, the reference minimum-loss incidence and deviation angles can be modified with additional corrections from different factors, as shown in Equations (18) and (19):…”
Section: Corrections For Off-reference Conditionsmentioning
confidence: 99%
“…Yet a detailed understanding of the flow features inside the critical components is essential for a reliable prediction of the overall performance, especially in severe off-design operating conditions. Available detailed experimental and numerical studies, conducted on a compressor cascade (Zachos et al, 2011) and on a contemporary high-bypass ratio turbofan in an altitude test cell (Prasad and Lord, 2010) indicate that, in windmilling operation, the fan stage operates under severe off-design (negative) angle-of-attack conditions, leading to the development of flow separation on both rotor and stator. These observations were confirmed by a previous experimental study on a small, geared turbofan, at ground level (García Rosa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the increasing fidelity and reliability of numerical solvers encourages their use for studying the spray phenomena under conditions that are otherwise difficult to reproduce within an experimental environment. Examples of successful application of CFD studies can be found in Zachos et al (2011), Manzar et al (2009) and Chalet et al (2010). In this paper, results from a number of atomizer CFD simulations that were run at sub-atmospheric pressures are presented.…”
Section: Introductionmentioning
confidence: 99%